Dmaic-based sustainable value stream mapping methodology for sustainable manufacturing improvement - Jamil, Norhazrina (2020)
After the seminal report of “Our Common Future” as a normative reference, sustainability has significantly and unprecedentedly evolved over the years, unanimously accepting that being sustainable is more beneficial. The research was accordingly built upon the discussion concerning sustainable value stream mapping (Sus-VSM) which recently emerged with the purpose of advancing sustainable manufacturing systems. Research on this sustainable-oriented lean tool is considered to be limited. It involves constant implementation plans for continuous improvement at value-stream level. Therefore, due to the lack of a continuous improvement process, subsequent developmental maps of this value stream can be established to continue the cycle which has been highlighted as a notable shortfall in this context. To fill the gap, this research study presents the application of a unified improvement approach known as ‘Lean Six Sigma’ through the development of the DMAIC methodology (Define, Measure, Analysis, Improve and Control) on sustainable value stream mapping. The methodology is outlined in detail by providing well-defined processes for each phase in the DMAIC-based approach, while at the same time considering sustainability elements in each step. The methodology begins by defining the research objectives and identifying relevant sustainable metrics as well as establishing the Sus-VSM appropriately for the Measure phase. A comprehensive analysis of waste and improvement activity identification was carried out by utilizing the Six Sigma tools thus deriving the future state of Sus-VSM in the Improve phase. Continuous improvement activity by performance monitoring and institutionalization was carried out in the final phase. The developed methodology was practically validated with an industrial case study in order to support this narrow body of knowledge. The research findings is revealed that the DMAIC-based approach can be effectively applied to systematize sustainable value stream mapping in sustainable manufacturing by contemplating environmental, economic and social sustainability elements. Additionally, the improvement activities conducted have resulted significant waste reduction of 28% and 21% for the environmental metric in terms of chemical and energy consumption respectively, 17.3% of cycle time reduction for the economic metric, and 44.4% for the social metric. The study also provides a guiding reference for operation managers who wish to undertake similar improvement projects and make their manufacturing operations more sustainable.